A Study on the Effect of Portfolio Allocation on Mutual Funds - Mihir Dash; Rita Samikannu (Asian Journal of Finance & Accounting, 2024)
There are hundreds of mutual funds in the market, each offering different returns. The investors always look at funds which give high returns and have low risk. Thus while making a portfolio the asset management company should make investment allocations where returns are definite and to give justified returns for every rupee the investors pay, considering the different risks. The objective of the study was to find the short-term effects of portfolio allocation on the performance of mutual funds. The data for the study was consisted of the portfolio allocations and the performance statistics of one hundred and fifty-nine open-ended mutual funds, of which fifty were diversified debt/ income funds and one hundred and nine were diversified equity funds. These funds were further classified into different mutual fund schemes. Each of the mutual funds had a different portfolio and investments were made in different instruments like bonds, certificates of deposit, commercial papers, etc. (in case of debt) and in different sectors like technology, chemicals, services, etc. (in case of equity). The findings from the study indicate that, for debt funds, allocation in bonds and government securities tend to impact the performance of the fund, while for equity funds, allocation in engineering, energy, and service sector stocks tend to impact the performance of the fund.